Advances in multifunctional biomass-derived nanocomposite films for active and sustainable food packaging. (1st February 2023) - Shi, Jiabo; Zhang, Ruizhen; Liu, Xiaochen; Zhang, Yuxuan; Du, Yuxin; Dong, Huahua; Ma, Yutian; Li, Xiaojie; Cheung, Peter C.K.; Chen, Feng
Abstract: Innovative food packaging techniques provide extrinsic systems for ensuring the quality and safety of food products. Recent research has focused on the development of multifunctional nanocomposites towards emerging active and sustainable food packaging (ASFP) systems. Specifically, diverse biomass-derived nanocomposite films (BNFs) are engineered via incorporating functional nanomaterials into the naturally-occurring biopolymers (e.g., polysaccharides and proteins). Such BNFs lead to minimum environmental risks compared to petroleum-derived materials, while exhibit improved physicochemical properties and functionalities, demonstrating great potential for ASFP. This review provides a summary of state-of-art BNFs based on their composition and application. We also highlight the advantages of BNFs for agricultural products. Particularly, the interactions between the biomass matrix and the nanomaterials are discussed to provide insightful rationales for designing high-performance BNFs. We envision that BNFs will not only be emerged as the dominant food packaging materials, but also contribute to the international trade and addressing the global food crisis. Graphical abstract: Unlabelled Image